Rural youth facing the "Agri-food Giant" in Jalisco, México. Reflections on environmental impact and intergenerational justice - SÁNCHEZ-SÁNCHEZ, David (Utopía y Praxis Latinoamericana, 2023)
Some socio-environmental effects on the new generations in rural areas, specifically on rural youth, are addressed, recognizing the impacts of the implementation of an agro-industrial strategy named "Jalisco. Mexico's Agrifood Giant". Some state laws related to sustainable development, agribusiness, as well as children and youth, were reviewed, since a strategy of this type has consequences that will accumulate and be felt in the following generations. A local experience with rural children and youth is shown, from which questions arise about agribusiness in a community dedicated to corn monoculture. Documenting some effects of the use of pesticides on children and youth. It concludes with some reflections on the urgency of new ways of understanding environmental justice in its intergenerational dimension, to address the problems arising from the imposition of the global agrifood system.